Membangun Master Plan Teknologi Informasi Dengan Metode Ward and Peppard - I Dewa Gede Putra Widiana; I Gede Juliana Eka Putra; I Nyoman Yudi Anggara Wijaya (STMIK Banjarbaru, 2021)
The Keramas village government, Gianyar regency, Bali has not carried out strategic ICT planning through developing e-Government to adjust the increase in the value of government organizations, while on the one hand the preparation of the ICT master plan at the village government office can be used as a government reference in determining policy. This paper presents an information technology master plan in Keramas Village, Gianyar. The method used to develop this information technology master plan is ward and peppard. The input stages consist of internal business environment analysis, external environmental analysis, internal IS/IT analysis and internal IS/IT environmental analysis. In this method also used Value Chain analysis, SWOT analysis, and Mc analysis. Farlan Grid. The output of the system is in the form of an IT strategy that provides recommendations to the Keramas Village Office to implement information technology in accordance with the existing implementation plan.Keywords: ICT Master Plan, Strategic Plan, Ward and Peppard Method ABSTRAK. Pemerintahan desa Keramas kabupaten Gianyar Bali belum melakukan perencanaan strategis TIK melalui mengembangkan e-Government untuk menyesuaikan peningkatan nilai organisasi pemerintahan, sementara di satu sisi penyusunan master plan TIK pada kantor pemerintahan desa dapat dijadikan sebagai acuan pemerintahan dalam penetuan kebijakan. Paper ini menyajikan master plan teknologi informasi di Desa Keramas Gianyar. Metode yang digunakan untuk membangun master plan teknologi informasi ini adalah ward and peppard. Tahapan masukan terdiri atas analisis lingkungan bisnis internal, analisis lingkungan eksternal, analisis SI/TI internal dan analisis SI/TI lingkungan internal. Dalam metode ini juga digunakan analisis Value Chain, analisis SWOT, dan analisis Mc. Farlan Grid. Luaran sistem berupa staretgi TI yang memberikan rekomendasi kepada Kantor Desa Keramas untuk menerapkan teknologi informasi sesuai dengan rencana implementasi yang ada.Kata kunci: Master Plan TIK, Rencana Strategi, Metode Ward and Peppard